Análise do consumo de álcool em pacientes submetidos a transplante de fígado - Melo, Patrícia Silva (2015)
Liver transplantation is considered an effective treatment for end-stage liver diseases related or not related to alcohol intake. Recidivism is one of the most frequent drug abuses and the excessive alcohol intake has a negative impact in the life quality of the transplanted patient. Goals: Analyze the alcohol intake in the life quality context of the liver transplanted patients, verify the alcohol intake in these patients sample at Hospital de Base de São José do Rio Preto – SP, analyze the transplanted profiles according to their alcohol intake, evaluate the quality of life after the liver transplantation and the alcohol intake predictors. Method: Cross-sectional, observational and descriptive study from January of 1998 to march of 2014 including 124 adult patients who underwent to liver transplantation. All the transplanted patients and the ones followed for more than six months were included and those who were inaccessible to answer to the questionnaire (49) or who were under treatment for Hepatitis C (6) were excluded. Three instruments were used for the data collection: 1- questionnaire about the perception of the patient regard to the post-transplant overall health, 2- SF-36 quality of life questionnaire and 3- AUDIT-C questionnaire for substance intake. Were studied 124 patients divided in groups according to AUDIT-C classification, in which 29 were alcoholic and 95 were abstainers. From the 29 alcoholic patients, 22 were excessive alcohol consumers and 7 were acceptable. Among the 29 alcoholic patients, 14 had recidivism (had ALD as a cause of cirrhosis) and 15 had no recidivism (de-novo). From the 14 patients with recidivism, 11 had excessive alcohol intake and 3 had acceptable alcohol intake. Among the 15 patients with no recidivism, 11 had excessive alcohol intake and 4 had acceptable alcohol intake. Based on an analysis of factors that could be predictors of the post transplantation alcohol consumption were analyzed: prior and post-transplant marital status, level of education, household income, prior and post-transplant job, prior and post-transplant family relationship, prior and posttransplant social relationship, post-transplant daily change, prior and post-transplant humor, prior and post-transplant quality of sleep, prior and post-transplant eating, prior and post-transplant tobacco use, prior and post-transplant alcohol intake, prior and post-transplant drugs use, prior and post-transplant complications of the disease, treatment for other diseases and transplant changing. The same questions were asked to the family members for collateral information. Results: The overall health, physical aspects and emotiona aspects were identified regarding to the quality of life. In addition, more acceptable male consumers related to alcohol intake, the time of transplantation, smoking, nourishment and marital status were also identified. Conclusion: It was observed significant and excessive alcohol consumption in liver transplanted patients with or without previous alcoholic cirrhosis. The analysis of predictor factors should be done with all the patients and not only with the patients with previous alcoholism, because we found patients with recidivism and alcoholic (de-novo) patients in similar proportions, as well as the similar prevalence of excessive alcohol intake in both groups.